Combined cooling, heating, and power systems : modeling, optimization, and operation - Shi, Yang, 1972-; Liu, Mingxi, 1988-; Fang, Fang, 1976- (John Wiley & Sons, 2017)
This book was written by an international author team at the forefront of combined cooling, heating, and power (CCHP) systems R & D. It offers systematic coverage of state-of-the-art mathematical modeling, structure optimization, and CCHP system operation, supplemented with numerous illustrative case studies and examples.
Keywords: Cogeneration of electric power and heat.; Cooling systems.; Heating.; elektronické knihy; electronic books